The effects of sovereign risk: A high frequency identification based on news ticker data - Ruben Staffa (Halle Institute for Economic Research (IWH), 2022)
This paper uses novel news ticker data to evaluate the effect of sovereign risk on economic and financial outcomes. The use of intraday news enables me to derive policy events and respective timestamps that potentially alter investors' beliefs about a sovereign's willingness to service its debt and thereby sovereign risk. Following the high frequency identification literature, in the tradition of Kuttner (2001) and Guerkaynak et al. (2005), associated variation in sovereign risk is then obtained by capturing bond price movements within narrowly defined time windows around the event time. I conduct the outlined identification for Italy since its large bond market and its frequent coverage in the news render it a suitable candidate country. Using the identified shocks in an instrumental variable local projection setting yields a strong instrument and robust results in line with theoretical predictions. I document a dampening effect of sovereign risk on output. Also, borrowing costs for the private sector increase and inflation rises in response to higher sovereign risk.
urn:nbn:de:gbv:3:2-866007
Keywords: C36; E43; E62; 330; high frequency identification; instrument; local projections; sovereign risk; text data